Vegetation-mediated assembly of rhizosphere fungal communities and their ecological drivers in constructed wetland systems - Deng, Nan; Tian, Yuxin; Song, Qingan; Niu, Yandong; Ma, Fengfeng (Frontiers in Microbiology, 2026)
IntroductionConstructed wetlands (CWs) are widely applied for restoring degraded wetland ecosystems and enhancing pollutant removal. Rhizosphere fungal communities play a crucial role in these ecosystems by mediating nutrient cycling and pollutant degradation.MethodsThis study examined the diversity patterns and assembly mechanisms of rhizosphere fungal communities across seven different CW types with distinct vegetation compositions within a farmland-to-wetland conversion system.ResultsWe identified 6,243 operational taxonomic units (OTUs), with sequencing coverage exceeding 98% across all vegetation types. Significant differences in phylogenetic diversity were observed between vegetation types. The dominant fungal classes were Sordariomycetes and Glomeromycetes, with ternary plot analysis indicating that different plant species selectively enriched distinct fungal lineages. Soil physicochemical properties, including pH, salinity, organic matter content, total potassium, and available phosphorus, showed significant variation across the different vegetation types. These soil factors were strongly correlated with the composition and diversity of rhizosphere fungal communities. Beta nearest taxon index (β MNTD) analysis indicated that both deterministic and stochastic processes contributed to community assembly, with stochastic processes exerting a stronger influence. The iCAMP model revealed that dispersal limitation was the primary factor influencing community assembly (57.13%), followed by homogeneous selection (20.53%) and drift processes (19.91%). Mantel tests showed that key environmental factors at key as soil nutrient levels, enzyme activities, and plant biomass was significantly associated with specific fungal lineages and community structure.DiscussionThese findings provide new insights into ecological processes that govern rhizosphere fungal community assembly in CWs, thereby advancing the evaluation of wetland restoration effectiveness and informing microbial management strategies to optimize ecosystem services and pollutant removal in CW systems.